БИОЦИДНЫЕ ЦЕМЕНТЫ - В.Т. , Ерофеев; А.И. , Родин; В.Ф., Смирнов; А.Д. , Богатов; С.В., Казначеев; Е.Н. , Сураева; М.А., Родина (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
The urgency of working out of biocidal cements is described in work; the way of giving cements foungicide and bactericidal properties is offered; efficiency of the application, of biocidal additives developed in the Mordovian State University of N.P.Ogaryov is confirmed; results of experimental researches of physicomechanical properties of the cements modified by developed biocidal additives are presented.